A tale of hidden cities - Anastasia Panori (REGION, 2017)
Hidden cities within a city? During the last decade there is a large trending literature concerning urban and suburban poverty concentration patterns. However, few are the cases where adequate data exist at a low spatial level, in order for scientists to explore that kind of socio-spatial phenomena. This paper tries to investigate the evolution of poverty within urban and suburban space, under a multidimensional framework, during a period of severe economic crisis and austerity measures. The metropolitan area of Athens is used as our case study, for which available data at a municipal level enable the calculation of the Multidimensional Poverty Index (MPI) for the years 2006 and 2011. Using cluster analysis based on the MPI values, three groups of municipalities are derived within Athens. For each one of them, a mean MPI index is calculated and then decomposed. The results indicate that there is a clear spatial concentration of poverty in the west suburban areas of Athens. The urban core of the city is characterised by middle-income municipalities, whilst the north-east and the south-east suburban areas experience low-poverty indicators. Finally, the results suggest that during the economic crisis period poor areas were affected the most.
Keywords: 330; urban poverty; multidimensional poverty index; Athens